Browning development in bakery products: A review - Purlis, Emmanuel (2010)
This paper presents a review regarding several aspects of the development of browning during baking of bakery products, mainly from an engineering point of view. During baking, the formation of colour is due to the Maillard reaction, and caramelization of sugars. Besides the major influence of this phenomenon on the initial acceptance of products by consumers, it is the responsible for other relevant changes occurring in food during baking, i.e. production of flavour and aroma compounds, formation of toxic products (e.g. acrylamide), and decrease of nutritional value of proteins. As well as baking, the development of browning in bakery products is a simultaneous heat and mass transfer process that occurs mostly in a non-ideal system under non-ideal conditions. In addition, the mechanisms of chemical reactions involved are still not elucidated completely, so the process is difficult to control and represents a major challenge for food engineers. Effects of browning on properties of products and experimental, modelling and technological aspects of colour formation during baking are reviewed.